Analisis Kemampuan Menggunakan Teks Bahasa Baku Berdasarkan Kaidah Ejaan Bahasa Indonesia (EBI) oleh Siswa Kelas X SMK Swasta Jambi Medan - Elisa Permata Sari; Rosmawati Harahap (Jurnal Akuntansi, Manajemen dan Ekonomi Digital, 2021)
The research was carried out with the aim of describing the mastery, application, and use of Indonesian Spelling in standard language texts based on EBI rules by students of class X TKJ-1 SMK Swasta Jambi Medan in Academic Year 2021-2022. This study used a quantitative descriptive method with a population of 145 people and a sample of 37 people. The total sample is 25% of the total population. The score of the highest student is equal to 85 while the lowest score is 60. Based on the results of data analysis, the average mastery, application, and use of EBI by students class X TKJ-1is equal  to 66.62 (30%) which is categorized as "fairly capable". The ability to use standard language texts based on the EBI rules by students of class X TKJ-1 tests based on standard language knowledge tests based on dictation is equal to 66.01 (38%) which is included in the "fairly capable" category. The results of the standard language text writing test according to the EBI rules and the standard language writing test based on dictation are equal to 66, 315 (quite capable). Thus, it can be concluded that the analysis of the calculation of the two types of standard language writing tests according to the EBI rules for students of class X TKJ-1 SMK Swasta Jambi Medan in Academic Year 2021-2022 are means 66, 315. The average score of students in class X TKJ-1 SMK Swasta Jambi Medan in Academic Year 2021-2022 is the same as 66,315 qualified into the category C grade (fairly capable).Keywords: analisys, ability, standard language text, rule of EBI